Tafsir Ayat-Ayat tentang Keuangan dan Pembiayaan - Rahmad Hidayat; Irgi Anggi Vahlevi Silaen; Mustika Adriana; Nirwan Nirwan (Al-Ulum: Jurnal Pendidikan Islam, 2020)
Islam is the true religion and regulates the life of mankind in this world and the hereafter. Islam also teaches various things in regulating life, such as managing or managing finances and financing in life. In the world of education, one must also be wise in managing finances and financing within the scope of education. The Alquran also describes management, stpenjelasanng from planning (planning), organizing (organizing), implementing (actuating), to controlling (controlling). By examining more deeply in the alquran, it will confirm the instructions contained in the alqu'an as guidelines for hudup for mankind. Keywords: Management Verses, Hadith, Tafseer